Percutaneous Coronary Intervention in the Elderly - Walsh, Simon J (The Ulster Medical Society, 2007)
OBJECTIVE: To determine the clinical risks and procedural outcomes for elderly patients undergoing percutaneous coronary intervention (PCI). METHOD: A retrospective case-load analysis was performed of all patients over the age of 80 years, undergoing PCI, over a two-year period, in a tertiary referral hospital. Patient demographics, procedural details and in-hospital complications were obtained by reviewing patient notes. Twelve-month outcomes were obtained from telephone follow-up to the general practitioners and all surviving patients. RESULTS: There were 55 procedures. Procedural risk was high, with a median TIMI risk score of four (IQR 3-6) and a median additive EuroSCORE of nine (IQR 8-10). There was a 95% angiographic success rate. There were no in-hospital complications. Median Canadian Cardiovascular Society angina class fell from four (IQR 3-4) to one (IQR 0-1). At one year there were twelve deaths (10 cardiovascular), eight of these occurred in patients who had incomplete revascularisation. CONCLUSION: PCI can be performed in an elderly, high-risk population with a low in-hospital mortality and marked symptomatic benefit. However, there is a significant 1-year mortality, particularly in patients who are only suitable for partial revascularisation.